A retrospective evaluation of the GDF/Suez merger: Effects on gas hub prices - Elena Argentesi; Albert Banal-Estanol; Jo Seldeslachts; Meagan Andrews (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
We present an ex-post analysis of the effects of GDF's acquisition of Suez in 2006 created one of the world's largest energy companies. We perform an econometric analysis, based on Difference-in-Difference techniques on the market for trading on the Zeebrugge gas hub in Belgium. Removing barriers to entry and facilitating access to the hub through ownership unbundling were an important part of the objectives of the remedies imposed by the European Commission. Our analysis shows a price decline after the merger. This decline suggests the remedies were effective in limiting the potential anti-competitive effects of the merger. Moreover, it suggests that ownership unbundling has generated improved access to the hub. Therefore, the remedies may have done more than simply mitigate the potential anticompetitive effects of the merger; they may have effectively created competition.
Keywords: L4; Q4; 330; Mergers; Ex-post Evaluation; Gas sector; Hub prices